Inspired by nature: printing revolution - Blasco, Eva (Ruperto Carola, 2022)
More than 500 years after Johannes Gutenberg invented his printing press, we are in the middle of a new printing revolution: 3D printing, also known as additive manufacturing. 3D printing is the process of creating a 3D object from a digital file. Thanks to recent advances in the field, we are now able to print a range of materials including metals, ceramics, polymers and even biological materials. Combining molecular engineering with state-of-the-art 3D printing techniques, materials scientists today are developing new printable materials that emulate the characteristics and behaviour of living systems. Current endeavours at Heidelberg University revolve around 3D printable materials that react to external stimuli like light, heat or electrical/magnetic fields, and that are able to change their properties over time.